2017
DOI: 10.1038/nmeth.4263
|View full text |Cite
|
Sign up to set email alerts
|

SCnorm: robust normalization of single-cell RNA-seq data

Abstract: SummaryNormalization of RNA-sequencing data is essential for accurate downstream inference, but the assumptions upon which most methods are based do not hold in the single-cell setting. Consequently, applying existing normalization methods to single-cell RNA-seq data introduces artifacts that bias downstream analyses. To address this, we introduce SCnorm for accurate and efficient normalization of scRNA-seq data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
227
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(234 citation statements)
references
References 26 publications
2
227
0
Order By: Relevance
“…Clustering using this approach was highly consistent with an alternative approach (Figure S1E) (Bacher et al, 2017). Furthermore, additional t-SNE analyses with multiple perplexity parameters (15, 20, 25, 30 and 35) and six instances for each perplexity parameter confirmed the robustness of the clustering patterns (data not shown).…”
Section: Star Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…Clustering using this approach was highly consistent with an alternative approach (Figure S1E) (Bacher et al, 2017). Furthermore, additional t-SNE analyses with multiple perplexity parameters (15, 20, 25, 30 and 35) and six instances for each perplexity parameter confirmed the robustness of the clustering patterns (data not shown).…”
Section: Star Methodssupporting
confidence: 77%
“…The relative expression levels, across the remaining subset of cells and genes, were used for downstream analysis. Although normalization approaches can potentially introduce bias into initial clustering, relative expression levels, as defined above and as defined with an alternative normalization method (Bacher et al, 2017) were highly similar. The use of alternative normalization had a limited influence on downstream results such as the distribution of p-EMT scores (data not shown).…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BigSCale presents a complete standalone package combining the aforementioned analysis steps. Of note, bigSCale can be used in combination with external normalization tools (Lun et al 2016;Bacher et al 2017), as we have shown for scran normalization applied to our simulated data sets (Supplemental Fig. S6).…”
Section: Discussionmentioning
confidence: 92%
“…Although it has the advantage of being able to profile the complete transcriptome, the abundance of lowly expressed transcripts like transcription factors remains a challenge and requires pooling of data when the magnitude of change is also small. Recent reports have aimed to improve the analysis algorithms and to extract more information out of the data [7376]. Since the cells are lysed to retrieve the mRNA, scRNA-seq ideally provides a snapshot of the cell state, inferred by the transcript profile.…”
Section: Integration Of Protein Detection and Transcriptional Profilimentioning
confidence: 99%